Monocrotaline Induces Endothelial Injury and Pulmonary Hypertension by Targeting the Extracellular Calcium–Sensing Receptor. Issue 4 (April 2017) - Xiao, Rui; Su, Yuan; Feng, Tian; Sun, Mengxiang; Liu, Bingxun; Zhang, Jiwei; Lu, Yankai; Li, Jiansha; Wang, Tao; Zhu, Liping; Hu, Qinghua
Abstract : Background: Monocrotaline has been widely used to establish an animal model of pulmonary hypertension. The molecular target underlying monocrotaline‐induced pulmonary artery endothelial injury and pulmonary hypertension remains unknown. The extracellular calcium–sensing receptor (CaSR) and particularly its extracellular domain hold the potential structural basis for monocrotaline to bind. This study aimed to reveal whether monocrotaline induces pulmonary hypertension by targeting the CaSR. Methods and Results: Nuclear magnetic resonance screening through WaterLOGSY (water ligand‐observed gradient spectroscopy) and saturation transfer difference on protein preparation demonstrated the binding of monocrotaline to the CaSR. Immunocytochemical staining showed colocalization of monocrotaline with the CaSR in cultured pulmonary artery endothelial cells. Cellular thermal shift assay further verified the binding of monocrotaline to the CaSR in pulmonary arteries from monocrotaline‐injected rats. Monocrotaline enhanced the assembly of CaSR, triggered the mobilization of calcium signaling, and damaged pulmonary artery endothelial cells in a CaSR‐dependent manner. Finally, monocrotaline‐induced pulmonary hypertension in rats was significantly attenuated or abolished by the inhibitor, the general or lung knockdown or knockout of CaSR. Conclusions: Monocrotaline aggregates on and activates the CaSR of pulmonary artery endothelial cells to trigger endothelial damage and, ultimately, induces pulmonary hypertension.